The fantastic flying books of Mr. Morris Lessmore - Joyce, William, 1957- (Atheneum Books for Young Readers, 2012)
Morris Lessmore loves words, stories and books, and after a tornado carries him to another land, dreary and colorless, he finds a single book in color that leads him to an amazing library where, he learns, the books need him as much as he needs them.